Pengembangan Critical Success Factor (CSF) untuk Menunjang Kinerja Pejabat Pembuat Komitmen (PPK) dalam Pembangunan Jembatan Ketapang di Banyuwangi - Tugiman Tugiman; Bambang Syairudin (Jurnal Bisnis dan Keuangan, 2018)
Bridge Project is a very complex work with high technology. In the project’s execution there are to many problem, such as delays of implementation, overpayment and other failures. It is necessary to develop of critical success factor (CSF) to support the performance of committing officer (PPK) in the execution of it’s duties and responsibilities in the implementation of the bridge project. The purpose of this study to identify the factors that are relevant to get an idea of the perception of CSF. The method used to solve complex problems in this study using analytical hierarchy process (AHP).The results of this study, the factors that affected the successful implementation of the bridge project, is the ability of the PPK in making self-estimated price (HPS) with the value (0,038), the ability of consultants to assist and provide guidance to the contractor in the licensing value ratio consistency (0,002) and the ability contractor in making the first project handover (PHO) value consistency ratio (0.001). The conclusion is that three factors are veryaffected to support the performance of committing officer (PPK) in the execution of bridge project.